PERAN PANITERA PENGGANTI DALAM PELAKSANAAN ASAS PERADILAN YANG CEPAT, SEDERHANA BIAYA RINGAN: Studi di Pengadilan Negeri Padang Kelas IA - Yetti, Arni (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The role of the substitute clerk in the implementation of the judicial principle that is fast, simple and inexpensive, as referred to in Article 45 of the Regulation of the Supreme Court of the Republic of Indonesia No. 7 of 2015 concerning the Organization and Work Procedure of the Registrar and Secretariat of the Court. The role of the criminal justice bureaucracy in the courts is very important to realize substantial justice because the Criminal Procedure Code adheres to a service model in the administration of criminal justice. The Substitute Registrar in the implementation of fast, simple, low-cost judicial principles at the Padang Class IA District Court is very decisive in the trial process to produce a quality decision to fulfill a sense of justice for the parties involved. The principle of a simple, fast and low-cost judicial system is one of the principles in the justice system in Indonesia as regulated in Article 4 Paragraph (2) of Law No. 48 of 2009 concerning Judicial Authority which reads